Climate-Related Financial Risks and Their Implications for Banking Stability and Investment Decision-Making - Alfa Rohmatin; Aswanto Aswanto; Marito Ritonga (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This empirical investigation employs a quantitative explanatory research design to systematically quantify the transmission pathways of environmental externalities onto banking performance metrics and corporate portfolio adjustments across major global financial hubs from two thousand fifteen through two thousand twenty five. Utilizing structural equation modeling and dynamic panel regressions estimated via maximum likelihood techniques, the analytical architecture maps the multi layered dependencies between climate related shocks and macroprudential stability indicators. The empirical findings reveal that transitional policy shocks significantly expand corporate asset volatility, forcing institutional fund managers to execute rapid capital withdrawals from carbon intensive operations and energy inefficient real estate trusts. Furthermore, the research confirms that cross border cultural variations and informational frictions heavily moderate investor behavioral traits during sudden regulatory reconfigurations. The diagnostic evaluation mathematically validates the proposed climate adjusted capital asset pricing framework, demonstrating strong model fit indices. Ultimately, the results underscore the critical necessity for central banking authorities to deploy progressive green prudential tools and standardized disclosure criteria to insulate international financial networks from compounding ecological risks.